Analisis Komparasi Performa Bohlam LED Berbagai Merk - Rahman Azis Prasojo; Hafiz Furqoni; Muhammad Fahmi Hakim; Hari Kurnia Safitri; Heri Sungkowo (Elposys: Jurnal Sistem Kelistrikan, 2020)
LED bulb are increasingly being adopted not only because of their good efficacy, but also because they are known to havehigh controllability. LED lighting has developed rapidly in recent years to achieve more efficient and reliable LED performance. Severalstudies have conducted experiments to obtain the characteristics and performance of LED lamps. However, study comparing theperformance of LED bulbs with various manufacturer and considering the price factor has not been found. In this study, the performancecomparison of six LED bulb manufacturers that are commonly found in the Indonesian market were conducted. Each brand is sampledfrom three rated powers. The results of this study show a weak correlation between the price and performance. Nonetheless, theperformance of LED bulb from different manufacturers were observed.